Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the roots of the quadratic equation \( x^2 - 4x + 3 = 0 \), we can use the quadratic formula, which is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, \( a = 1 \), \( b = -4 \), and \( c = 3 \).
1. First, identify the coefficients:
- \( a = 1 \)
- \( b = -4 \)
- \( c = 3 \)
2. Calculate the discriminant \( \Delta \) using the formula:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values:
[tex]\[ \Delta = (-4)^2 - 4 \cdot 1 \cdot 3 = 16 - 12 = 4 \][/tex]
3. Since the discriminant is positive (\(\Delta = 4\)), the quadratic equation has two distinct real roots.
4. Now, use the quadratic formula to find the roots. The solutions are:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} \][/tex]
Substituting the values:
[tex]\[ x_1 = \frac{4 + \sqrt{4}}{2 \cdot 1} = \frac{4 + 2}{2} = \frac{6}{2} = 3 \][/tex]
[tex]\[ x_2 = \frac{4 - \sqrt{4}}{2 \cdot 1} = \frac{4 - 2}{2} = \frac{2}{2} = 1 \][/tex]
Therefore, the roots of the equation \( x^2 - 4x + 3 = 0 \) are \( x = 3 \) and \( x = 1 \).
In terms of coordinates, these roots can be represented as the points where the equation \( y = x^2 - 4x + 3 \) intersects the x-axis:
- The coordinates of the first root are \( (3, 0) \).
- The coordinates of the second root are \( (1, 0) \).
So, the coordinates of the roots are [tex]\( (3, 0) \)[/tex] and [tex]\( (1, 0) \)[/tex].
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, \( a = 1 \), \( b = -4 \), and \( c = 3 \).
1. First, identify the coefficients:
- \( a = 1 \)
- \( b = -4 \)
- \( c = 3 \)
2. Calculate the discriminant \( \Delta \) using the formula:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values:
[tex]\[ \Delta = (-4)^2 - 4 \cdot 1 \cdot 3 = 16 - 12 = 4 \][/tex]
3. Since the discriminant is positive (\(\Delta = 4\)), the quadratic equation has two distinct real roots.
4. Now, use the quadratic formula to find the roots. The solutions are:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} \][/tex]
Substituting the values:
[tex]\[ x_1 = \frac{4 + \sqrt{4}}{2 \cdot 1} = \frac{4 + 2}{2} = \frac{6}{2} = 3 \][/tex]
[tex]\[ x_2 = \frac{4 - \sqrt{4}}{2 \cdot 1} = \frac{4 - 2}{2} = \frac{2}{2} = 1 \][/tex]
Therefore, the roots of the equation \( x^2 - 4x + 3 = 0 \) are \( x = 3 \) and \( x = 1 \).
In terms of coordinates, these roots can be represented as the points where the equation \( y = x^2 - 4x + 3 \) intersects the x-axis:
- The coordinates of the first root are \( (3, 0) \).
- The coordinates of the second root are \( (1, 0) \).
So, the coordinates of the roots are [tex]\( (3, 0) \)[/tex] and [tex]\( (1, 0) \)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.